2008
DOI: 10.1111/j.1872-034x.2008.00376.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and endoscopic features of gastric varices secondary to splenic vein occlusion

Abstract: ECDUS color flow images of gastric variceal flow depicted specific findings of gastric varices secondary to splenic vein occlusion. Treatment should take into account the diseases underlying these conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
(57 reference statements)
1
13
0
Order By: Relevance
“…Increased blood flow in these vessels dilates submucosal veins of the stomach, causing gastric varices that often do not demonstrate clinical symptoms, but can result in hypersplenism or gastrointestinal hemorrhage. Gastric varices due to splenic vein occlusion show a round fundal region at the center, with varices that expanded to the greater curvature of the gastric body 1214. However, neither portal vein thrombosis nor splenic vein thrombosis was evident on CT in this patient.…”
Section: Discussionmentioning
confidence: 66%
“…Increased blood flow in these vessels dilates submucosal veins of the stomach, causing gastric varices that often do not demonstrate clinical symptoms, but can result in hypersplenism or gastrointestinal hemorrhage. Gastric varices due to splenic vein occlusion show a round fundal region at the center, with varices that expanded to the greater curvature of the gastric body 1214. However, neither portal vein thrombosis nor splenic vein thrombosis was evident on CT in this patient.…”
Section: Discussionmentioning
confidence: 66%
“…There is a strong association between pancreatic diseases and splenic vein this condition may cause hypersplenism or gastrointestinal bleeding due to gastric varices. In previous studies of splenic vein occlusion, gastrointestinal bleeding has been reported to occur in 16-78% of patients [8,9,13,[21][22][23][24]. Sutton et al [9] found 53 cases of such occlusion, and reported a 64% incidence of upper gastrointestinal bleeding.…”
Section: Pathophysiology/symptoms Of Left-sided Portal Hypertensionmentioning
confidence: 99%
“…Additional images resulting from ECDUS color analysis of gastric variceal flow clearly depicted a round fundal region at the center, with varices that expanded to the curvatura ventriculi major of the gastric body on gastric varices due to splenic vein occlusion (Figures 3a and 3b) [23]. Variceal location of ordinary gastric varices was classified as fundal (located far from the cardiac orifice) and cardiac and fundal (located between the cardiac orifice and the fundus), however, there was no case with varices expanding to the curvatura ventriculi major of the gastric body with ECDUS findings of ordinary gastric varices [30].…”
Section: Diagnosis Of Gastric Varices Secondary To Left-sided Portal mentioning
confidence: 99%
See 1 more Smart Citation
“…SPH is a clinical syndrome of local portal hypertension induced by splenic vein thrombosis due to primary pancreatic diseases, which usually include chronic pancreatitis, pancreatic pseudocysts and pancreatic carcinomas [2]. Gastric variceal bleeding resulting from SPH of severe acute pancreatitis is quite rare especially in the acute stage, having been reported only sporadically, and the definitive therapeutic method of such lesions is sometimes difficult and controversial [6, 7]. …”
Section: Introductionmentioning
confidence: 99%